Effects of Red Mud and KCl Fertilizer Combination on Nutrient Availability and Growth of Maize (Zea mays L.) in Peatland Soils - Sulakhudin Sulakhudin; Surachman Surachman (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Tropical peatlands in West Kalimantan are severely constrained by extreme acidity (pH < 4.5), limiting maize productivity to 15 to 35% of genetic potential. Traditional peat burning exacerbates environmental degradation through CO₂ emissions and particulate matter release. This study evaluated red mud-KCl fertilizer combinations on soil nutrient availability and maize growth. A randomized complete block design examined five treatments with five replications (n = 25). Four treatment levels (R1 to R4) were applied with red mud doses (0.75 to 3.0 kg plot-1) with KCl fertilizer (42.6 g) versus controls. Red mud, an alkaline bauxite waste (pH 10 to 12), maintained heavy metal concentrations below regulatory thresholds. Statistical analyses employed ANOVA (α = 0.05) and Duncan’s Multiple Range Test. Treatments significantly elevated soil pH from 4.41 (control) to 5.45 to 5.67, transforming strongly acidic to moderately acidic conditions. Exchangeable K increased from 2.02 to 4.40 cmol(+) kg-¹, representing a 118% improvement in K availability. Available P improved by 13.4%, enhancing nutrient uptake capacity. The optimal treatment (R4: 3.0 kg red mud + KCl) demonstrated superior maize performance with significantly greater plant height, stem diameter, and maize ear weight than controls. Treatment R4 achieved the most favorable soil chemical properties, including optimal cation exchange capacity and nutrient retention, creating ideal growing conditions that maximized maize genetic potential expression in previously unproductive acidic peatland soils. Results indicate substantial potential for sustainable peatland agriculture through red mud-KCl soil amendments. Future investigations should assess long-term environmental sustainability, socio-economic viability, and farmer adoption mechanisms for implementing this amelioration strategy in tropical peatland systems.